Clinico-Radiological Diagnosis of Isolated Congenital Esophageal Stenosis in a Preterm Neonate - Sham, Minakshi (European Journal of Pediatric Surgery Reports, 2013)
A 2-day-old preterm female neonate weighing 1.6 kg and having excessive frothing from mouth was investigated for suspected esophageal atresia and tracheoesophageal fistula. X-ray findings of an unusually low-ending upper pouch (up to T8 level) and the absence of gas in abdomen lead to suspicion of an unusual variety of esophageal atresia. Hence unlike the usual management of pure esophageal atresia, in terms of esophagostomy and gastrostomy in neonatal period, right thoracotomy was performed allowing successful primary anastomosis. A high index of suspicion on the basis of radiological picture led to early diagnosis of a rare anomaly like congenital esophageal stenosis and successful management of this low birth weight baby.
Keywords: congenital esophageal stenosis (CES); esophageal atresia (EA); preterm low birth weight (LBW) neonate; primary resection anastomosis; radiological diagnosis